Preliminary studies of the possibility of using local cement in oil and gas wells cementing operations in Malaysia - Shahrudin, Shahrin; Samsuri, Ariffin; Ismail, Abdul Razak; Junin, Radzuan; Hashim, Ayob (Jawatankuasa Penyeldikan & Perundingan, Fakulti Kej. Kimia & Kej. Sumber Asli, UTM, 1992)

(untitled)
Calcareous and argillaceous materials are the raw materials used in making ordinary portland cements and portland cement class G with their main chemical compound consists of Tricalcium silicate, Dicalcium silicate, tricalcium aluminate and tetracalcium aluminoferrite. Currently the class g cement used for the oil and gas wells cementing operations is imported from other countries. To overcome this matter, the suitability studies of locally produced cement were carried out according to American Petroleum Institute (API) Specification method. Some of the test being run include determination of cement composition, free water density, fluid-loss rate, comprehensive strength and slurry thickening time. Generally, locally produced cement comply to the API Specification 10.